The Impact Of Family Support On Increasing Muscle Strength Rehabilitation Post-Stroke Adults In Bukittinggi City 2023 - Rinawati Kasrin; Faridah Mohd Said; Tukimin Sansuwito; Yendrizal Jafri; Rully Fadillah (Lembaga Pengembangan Kinerja Dosen, 2023)
Stroke is still the main cause of disability in the world. The impact of a stroke relies heavily on the location and extent of damage, and age. Post-stroke is the most difficult period for patients in they personal care. Family support is essential to increase confidence for rehabilitation in post-stroke patients. Rehabilitation in post-stroke patients is done so that post-stroke patients are able to perform daily activities independently. The aims of this study to determine the relationship family support with increasing muscle strength rehabilitation in post-stroke adult. The Method : This research was an analytical observational and was conducted in Bukittinggi City on July, 2023. The variables studied family support with muscle strength. This research is a quantitative research with Cross-sectional design. The population in this study were post-stroke patients 50 people and the sample amounted to 42 respondent. Results : The result of this research shows that there is a strong relationship between family support and increasing muscle strength in rehabilitation p-value 0.006<0.05. The conclusion is family support has impact to inceasing muscle strength rehabilitation of post-stroke adult patients. It is recommended for health workers to provide counseling to improve family support in curing stroke patients. The study confirms the importance of family support in terms of information support and awards support to the quality of life of patients with post-stroke.